Caracterización de los trabajadores cesantes en Colombia en el periodo 1992-2002, como fundamento para el diseño de una estrategia organizativa y financiera para la sostenibilidad de su aseguramiento en salud (2004)
ABSTRACT: Unemployment has been one of the main factors that have obstructed the achievement of universal health insurance in Colombia, just as Law 100 of 1993 proposed to reach. Those workers that had a history of labour life and lost their posts lack health insurance in a large percentage as well as their close relatives. In this way, they remain exposed to lose the family economical resources if any of the members requires health services he/she should pay for. Objective: the primary objective of this research was to establish the socio-economic characteristics of this population, its level of health insurance and the duration of the employment-unemployment cycle in the country. The results are to be used in a second phase that pretends to design and validate an intervention strategy to guarantee the maintenance of the health insurance of this population. Methods: it was a descriptive-retrospective study that used quantitative analysis techniques. Data was taken from official records of Colombian government, as well as from previous studies related with the matter. Results: principal finds show a persistent growing of participation of workers who lost their posts as part of the total unemployed population in the country. A high proportion of them (56%) have a medium educational level and a high percentage (57.8%) belongs to the medium socio-economic stratum. It is remarkable too that the mean duration of unemployment grew from 27.5 weeks in 1992 to 58.2 weeks in 2002.